Nanosheets of an Organic Molecular Assembly from Aqueous Medium Exhibit High Solid-State Emission and Anisotropic Charge-Carrier Mobility - Ghosh, Samrat (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.